If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12(x + -1) = 4(x + 13) Reorder the terms: -12(-1 + x) = 4(x + 13) (-1 * -12 + x * -12) = 4(x + 13) (12 + -12x) = 4(x + 13) Reorder the terms: 12 + -12x = 4(13 + x) 12 + -12x = (13 * 4 + x * 4) 12 + -12x = (52 + 4x) Solving 12 + -12x = 52 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + -12x + -4x = 52 + 4x + -4x Combine like terms: -12x + -4x = -16x 12 + -16x = 52 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + -16x = 52 + 0 12 + -16x = 52 Add '-12' to each side of the equation. 12 + -12 + -16x = 52 + -12 Combine like terms: 12 + -12 = 0 0 + -16x = 52 + -12 -16x = 52 + -12 Combine like terms: 52 + -12 = 40 -16x = 40 Divide each side by '-16'. x = -2.5 Simplifying x = -2.5
| 7=3w+4w | | 4x+2=-16 | | -15-49= | | s+(s+.89)=92.99 | | 2x+21=6x-9 | | 4(16+13)-2(3-4)=x-4 | | 4.1f+9.22=-12.10+2.9+8.15 | | 9x^2-9=31 | | 4(16+3)-2(3-4)=x-4 | | 2x+30=90 | | 6x+(5x-20)=90 | | p+p+33+3p-37=696 | | 12x+3=x+8 | | 10x-6ax+3=5a+3ax | | -2+x/-4=-14 | | z-8z=9z-8-z | | 9x+6y=-9 | | 250=50-3+b | | 6x+8-9(x+1)=4x+3 | | -(2x+1)-(3+4X)+5X=3x-8.9 | | -x/7=1/16 | | z-7z=6z-5-z | | 6x+5x+20=90 | | 15=x/5+7 | | x+.02x=22.73 | | y=b+50x | | x+.02x=22.23 | | f(x)=-0.022x^4-0.457x^3-2.492x^2-5.279x+87.419 | | Y=0x+7 | | 4s+6-2s=2(s+3) | | 5x^2+7=137 | | .3333333333(12-6x)=4-2x |